Continuous Kidney Replacement Therapy Practices in Pediatric Intensive Care Units Across Europe - Daverio, Marco; Cortina, Gerard; Jones, Andrew; Ricci, Zaccaria; Demirkol, Demet; Raymakers-Janssen, Paulien; Lion, Francois; Camilo, Cristina; Stojanovic, Vesna; Grazioli, Serge; Zaoral, Tomas; Masjosthusmann, Katja; et al. (JAMA network open, 2022)
IMPORTANCE: Continuous kidney replacement therapy (CKRT) is the preferred method of kidney support for children with critical illness in pediatric intensive care units (PICUs). However, there are no data on the current CKRT management practices in European PICUs. OBJECTIVE: To describe current CKRT practices across European PICUs. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional survey of PICUs in 20 European countries was conducted by the Critical Care Nephrology Section of the European Society of Pediatric and Neonatal Intensive Care from April 1, 2020, to May 31, 2022. Participants included intensivists and nurses working in European PICUs. The survey was developed in English and distributed using SurveyMonkey. One response from each PICU that provided CKRT was included in the analysis. Data were analyzed from June 1 to June 30, 2022. MAIN OUTCOME AND MEASURES: Demographic characteristics of European PICUs along with organizational and delivery aspects of CKRT (including prescription, liberation from CKRT, and training and education) were assessed. RESULTS: Of 283 survey responses received, 161 were included in the analysis (response rate, 76%). The attending PICU consultant (70%) and the PICU team (77%) were mainly responsible for CKRT prescription, whereas the PICU nurses were responsible for circuit setup (49%) and bedside machine running (67%). Sixty-one percent of permanent nurses received training to use CKRT, with no need for certification or recertification in 36% of PICUs. Continuous venovenous hemodiafiltration was the preferred dialytic modality (51%). Circuit priming was performed with normal saline (67%) and blood priming in children weighing less than 10 kg (56%). Median (IQR) CKRT dose was 35 (30-50) mL/kg/h in neonates and 30 (30-40) mL/kg/h in children aged 1 month to 18 years. Forty-one percent of PICUs used regional unfractionated heparin infusion, whereas 35% used citrate-based regional anticoagulation. Filters were changed for filter clotting (53%) and increased transmembrane pressure (47%). For routine circuit changes, 72 hours was the cutoff in 62% of PICUs. Some PICUs (34%) monitored fluid removal goals every 4 hours, with variation from 12 hours (17%) to 24 hours (13%). Fluid removal goals ranged from 1 to 3 mL/kg/h. Liberation from CKRT was performed with a diuretic bolus followed by an infusion (32%) or a diuretic bolus alone (19%). CONCLUSIONS AND RELEVANCE: This survey study found a wide variation in current CKRT practice, including organizational aspects, education and training, prescription, and liberation from CKRT, in European PICUs. This finding calls for concerted efforts on the part of the pediatric critical care and nephrology communities to streamline CKRT education and training, research, and guidelines to reduce variation in practice.
Keywords: průřezové studie; Infant, Newborn; Diuretics; Evropa; diuretika; Heparin; Europe; Child; Continuous Renal Replacement Therapy; jednotky intenzivní péče pediatrické; novorozenec; dítě; heparin; Intensive Care Units, Pediatric; Humans; lidé; Cross-Sectional Studies; kontinuální metody náhrady funkce ledvin